Tobacco and COVID-19: Molecular Interactions and Public Health Challenges – A Review - Chetan Vinay Deshmukh; Vibhuti Dilip Mistry; Arun Suresh Dodamani; Mayuri Bhikaji Nepale (International Journal of Virus Studies, 2025)
Tobacco use exacerbates health risks, making it a significant concern during the COVID-19 pandemic. Smoking has been implicated in the upregulation of ACE2 receptors, critical for SARS- CoV-2 entry, and contributes to immune dysregulation and oxidative stress, worsening clinical outcomes. Methods: This review synthesizes evidence on the molecular mechanisms linking tobacco and COVID-19, assesses risk factors, such as smoking status and comorbidities, and explores public health challenges in managing the dual burden of tobacco use and the pandemic. Results: Tobacco-induced ACE2 receptor up-regulation, impaired immune response, and oxidative stress exacerbate COVID-19 severity. Smokers exhibit higher rates of ICU admission, ARDS, and mortality. Public health challenges include disruptions in tobacco cessation efforts, with increased stress-related smoking and limited access to cessation programs during lockdowns. Discussion: The findings underscore the need for robust tobacco control policies integrated with COVID-19 management. Tailored cessation programs and strengthened regulations on tobacco marketing can mitigate risks. Conclusion: Tobacco cessation is crucial to reducing COVID-19 severity and strengthening public health resilience against future pandemics. Comprehensive policies and continued research are vital in addressing the combined burden of tobacco and infectious diseases.
Keywords: ACE2 expression; COVID-19; Tobacco use; immune modulation; public health challenges